2018
DOI: 10.7150/jca.22787
|View full text |Cite
|
Sign up to set email alerts
|

Increased Paxillin expression in prostate cancer is associated with advanced pathological features, lymph node metastases and biochemical recurrence

Abstract: Purpose Paxillin regulates cell-cell adhesion, and altered Paxillin expression has been associated with human carcinogenesis. This study analyzed the association between Paxillin expression in prostate cancer (PCa) tissues with clinicopathological features, lymph node metastasis and biochemical PCa recurrence.Methods A total of 386 tissue specimens from PCa patients who received radical prostatectomy and 60 tissue specimens from benign prostatic hyperplasia (BPH) cases were collected to construct tissue microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…It was also found that isolated carcinoma cells were not evident in the metastatic foci in the lymph nodes; thus, showing some degree of aggregation. Expression of paxillin, reported in prostate cancer ( 41 ) and involved in cancer cell aggregation ( 42 ), could be implicated to this observation; further studies are needed to clarify this relationship. The glomeruloid pattern was relatively rare in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…It was also found that isolated carcinoma cells were not evident in the metastatic foci in the lymph nodes; thus, showing some degree of aggregation. Expression of paxillin, reported in prostate cancer ( 41 ) and involved in cancer cell aggregation ( 42 ), could be implicated to this observation; further studies are needed to clarify this relationship. The glomeruloid pattern was relatively rare in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…In this regard, DUSP22, a member of the DUSP1 family which reduces JNK activation, negatively regulates cell migration through FAK dephosphorylation and inactivation in lung cancer cells [ 57 ]. Given that FAK and paxillin expression is elevated in prostate cancer and both proteins are associated with tumor progression, lymph node metastasis, and/or shortened survival [ 58 , 59 ], it is also plausible that in our cancer model, the paxillin/FAK pathway could contribute to the regulation of Snail expression by ERK and JNK. However, due to the difference between ERK- and JNK-dependent mechanisms, further research is required to investigate the molecular mechanisms underlying Snail regulation by these kinases.…”
Section: Discussionmentioning
confidence: 99%
“…Any discrepancies were resolved by re‐reviewing the sections. Two semi‐quantitative methods and the total LIMK1 immunostaining score methods including staining intensity and the proportion of positive cells were described as follows . The immunohistochemistry score of LIMK1 consists of two parts, including staining intensity and the proportion of positive cells.…”
Section: Methodsmentioning
confidence: 99%